1988
DOI: 10.1080/00207598808247780
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of Intelligence: A Comparison of Chinese Graduates From Chinese and English Schools in Hong Kong*

Abstract: The present study investigated the concepts of intelligence of two groups of Hong Kong Chinese university students. They differed in the secondary schools from which they graduated, one followed the Chinese system and the other the E n a s h system. These two groups were otherwise similar in age, academic achievement, and racial background. Subjects were asked to rate items selected from four popular intelligence tests in terms of their relevance to measuring intelligence and perceived difficulty. The relevanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Participants were first asked to estimate their overall intelligence, followed by Gardner's (1999) ten multiple intelligences (linguistic, logical-mathematical, spatial, musical, body-kinaesthetic, interpersonal, intrapersonal, existential, spiritual, and naturalistic intelligences), Sternberg's (1997) successful intelligences (adaptive, practical, and creative intelligences), and two items added specifically for the present study (nonverbal-logical intelligence and emotional intelligence). Nonverbal-logical intelligence was added because previous work has shown that Chinese respondents rate verbal skills as less important than their Western counterparts (Chen & Chen, 1988), whereas emotional 1 Although the distinction between individualism and collectivism remains one of the most prominent constructs in cross-cultural psychology (e.g., Vandello & Cohen, 1999), at least one recent review concluded that cultural differences these constructs "were neither as large nor as systematic as often perceived" (Oyserman, Coon, & Kemmelmeier, 2002). This appears to be an ongoing debate within cross-cultural psychology (e.g., see Schimmack, Oishi, & Diener, 2005), and our view here is that collectivism is likely to be related to lower SAI, as evidenced in previous work (e.g., Furnham et al, 2001;Yuen & Furnham, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were first asked to estimate their overall intelligence, followed by Gardner's (1999) ten multiple intelligences (linguistic, logical-mathematical, spatial, musical, body-kinaesthetic, interpersonal, intrapersonal, existential, spiritual, and naturalistic intelligences), Sternberg's (1997) successful intelligences (adaptive, practical, and creative intelligences), and two items added specifically for the present study (nonverbal-logical intelligence and emotional intelligence). Nonverbal-logical intelligence was added because previous work has shown that Chinese respondents rate verbal skills as less important than their Western counterparts (Chen & Chen, 1988), whereas emotional 1 Although the distinction between individualism and collectivism remains one of the most prominent constructs in cross-cultural psychology (e.g., Vandello & Cohen, 1999), at least one recent review concluded that cultural differences these constructs "were neither as large nor as systematic as often perceived" (Oyserman, Coon, & Kemmelmeier, 2002). This appears to be an ongoing debate within cross-cultural psychology (e.g., see Schimmack, Oishi, & Diener, 2005), and our view here is that collectivism is likely to be related to lower SAI, as evidenced in previous work (e.g., Furnham et al, 2001;Yuen & Furnham, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in one study different ethnic groups have been found to feature different conceptualizations of "intelligence"-even though they all lived in North Carolina and were subjected to the same cultural mainstream (Heath, 1983). As another example, in Chinese culture, nonverbal reasoning has been found to be rated as more relevant to intelligence than verbal reasoning (Chen & Chen, 1988). Ultimately, intercultural differences in implicit theories can make it difficult to carry out meaningful comparisons of ability test scores across cultures (Greenfield, 1997).…”
Section: Theoretical and Empirical Framework Explicit And Implicit Thmentioning
confidence: 99%
“…Henrich, Heine, and Norenzayan (2010) dubbed the common study sample as WEIRD (participants from Western, Educated, Industrialized, Rich, and Democratic societies). Cultural differences can be expected to play a huge role, in particular regarding conceptions of intelligence (Chen & Chen, 1988;Heath, 1983;Nisbett, 2003;Sternberg & Kaufman, 1998), test performance (through stereotype threat; e.g., Steele, 1997;Steele & Aronson, 1995), and the importance of selfimpression management (Heine, Lehman, Markus, & Kitayama, 1999). In many Eastern (i.e., primarily Asian) countries, for instance, social interaction abilities are considered to be more important than individual cognitive abilities (e.g., Nevo & Khader, 1995).…”
Section: Critical Aspects Of the Present Meta-analysismentioning
confidence: 99%
“…They are not 172 STERNBERG alone: Some prominent Western theorists have pointed out the importance of depth of processing for full command of material. Chen and Chen (1988) varied only language. They explicitly compared the concepts of intelligence of Chinese graduates from Chinese-language versus English-language schools in Hong Kong.…”
Section: Implicit Theories Of Intelligence Across Culturesmentioning
confidence: 99%